PEMBERDAYAAN IBU RUMAH TANGGA DALAM MENCIPTAKAN PRODUK EKONOMI KREATIF - Mutiara Eka Putri; Tulus Suryanto; Hanif Hanif (LPPM Universitas Bina Bangsa, 2023)
This community service aims to empower homemakers to create creative economic products like date-flavored tomatoes. It is hoped that this creative economy product can improve welfare and increase the economic empowerment of families, especially homemakers. The research methods include surveys, training, mentoring, and product development. The active participation of homemakers in every stage of the research is the key to achieving the goal of empowering the creative economy. The research results show that through intensive training and mentoring, homemakers can create creative economic products in the form of date-flavored tomatoes with high selling value. This product can be sold locally and in broader markets, increasing family income and expanding employment opportunities for homemakers. Empowering homemakers in creating creative economic products in the form of date-flavored tomatoes is an effective strategy for increasing the community's economic potential inclusively, increasing family economic independence, and encouraging the development of local products with high added value